Eficácia da intervenção assistida por animais na autopercepção de saúde, autoestima, sintomas depressivos e qualidade de vida relacionada à saúde em idosos residentes em instituição de longa permanência - Queiroz, Renata Coelho Freire Batista (2014)
Introduction: Population aging and changes in family dynamics have taken a greater number of people residing in long term care facilities, it has reflected in the quality of life of elderly. Some non-drug and low cost therapies have proved effective in bringing therapeutic benefits for the elderly such as Animal Assisted Intervention (AAI). Purpose: Evaluate the effectiveness of the AAI in self-rated health, self-esteem, depressive symptoms and health related quality of life in elderly nursing home residents. Methods: This study was approved by Ethics Committee of PUCRS and followed the rules of Resolution 466/ 12 of the National Board of Health. In this clinical study, forty-two elderly were randomly and distributed into two groups, consisting of 21 elderly each. To the Intervention Group (IG) it was suggested the use of animal assisted intervention. Control Group (CG) maintained the regular activities of the institution. The research was conducted in three stages: first it was done an initial assessment for both groups, twelve weeks using animal assisted intervention for IG, and GC was followed-up, and final assessment was applied for two groups. The following instruments were used, the Mini Mental State Examination, Self-rated Health Evaluation, Rosenberg Self-esteem Scale, Short Geriatric Depression Scale, Health Related Quality of Life Questionnaire SF 6D, data sheet including socioeconomic and health data, a Questionnaire to verify how was the experience with animals in the past and IG also did a questionnaire about the experience with AAI. The level of significance adopted was 5% (P<0,05).The absolute and relative frequencies and standard deviations were obtained. Continuous variables were described by mean and standard deviation or median and interquartile range. Results: It was found that the groups were homogeneous in all analyzed aspects, except age, which difference was significant (p = 0.007). After AAI there was a significant improvement in self-rated health for IG (p=0,021), but this improvement didn´t sustained after adjusting age (P=0,052). Comparing IG with CG there was a significant difference (P=0,010), even after adjusting age (p=0,009). It was noted significant improvement in self-steem to IG (p<0,001), but it got worse in CG (P=0,014). When comparing the groups the difference it was statistically significant (p<0,001), even after adjusting age (p<0,001). It was noted statistically relevant reduction in the average values of GDS for IG (P<0,001). When comparing the groups, the difference was significant (p<0,001) even after adjusting age (P<0,001). In both groups a percentage variation among the elderly who had depressed symptoms did not have statically significance. It was noted improvement in Health Related Quality of Life for IG (p<0,001). Otherwise the Control group got worst in this score (p=0,013). There was a statically significant difference between two (P<0,001), even after adjusting age (p<0,001). In case of associations among scales it was observed significant association between GDS and SF- 6D, self-esteem and SF- 6D, and self-rated health and GDS. In the CG it was observed significant relation between self -esteem and GDS. Conclusion: The results point out that IAA has improved the self-esteem, depressed symptoms and health related quality of life of the elderly resident of long-term care facilities.